Calibration of ultrasonic phased arrays for industrial applications - Ingram, M.; Gachagan, A.; Mulholland, A. J.; Nordon, A.; Dziewierz, J.; Hegarty, M.; Becker, E. (2017 IEEE SENSORS, 2017)
This paper investigates the consistency in phased array element performance by extracting information from the Full Matrix Capture (FMC) of a reflection from a planar interface. The purpose of this work is to generate a robust methodology for tracking phased array performance over time, therefore, ensuring the reliability of measured data. To achieve this, a calibration method has been developed that quantifies the pulse length, sensitivity, bandwidth and phase error for each element in the array. This paper will highlight the variation across individual array elements and the experimental variation across FMC replicates. Finally, to illustrate the impact of the element performance variation, the phase error is included within the Total Focussing Method imaging algorithm, resulting in an 8% increase in ultrasonic image resolution.